Development of UAV SOS flight combat reconnaissance mission program - Bayramov, A. A.; Hashimov, E. G. (Національний технічний університет "Харківський політехнічний інститут", 2019)
Systemof systems (SoS) conception for dynamic objects group have been become a very important direction in various areas on science and industry, including military. SoS is consisted of components which solve one task and on the whole jointing own properties and possibilities these components creat the complex system with new qualities. SoS is such system which during various operations combines and joints itself a synergetics of comands, control functions, network and feedback information change. In given paper, development of the combat task program of Unmanned Aerial Vehicles System of Systems offered version has been presented. Usually, the land control center manage UAVs by using of radio wireless. But it has shortcomings: 1) a radio wireless can be destroy, and in the best case UAV does not emplement task and self returns base; 2) an enemy taps the radio wireless and carry out UAVs control. The creation of SoS onthe basis of UAVs eliminates these flaws. In accordance with written in memory software program, UAVs SoS isself-controlled by infra-red (IR) wireless using “feedback” principle and it implement combat task independently. If some of UAVs loss IR-wireless then it (or they) return land control center independently. If some of UAVs is destroyed under enemy fire then other UAVs continue to implement a combat task. The Hamilton equations of motion of the given system has been obtained. The IR wireless between UAVs, radio wireless between UAVs and land control post, and UAVs flight control conditions havebeen offered. It is shown that Unmanned Aerial Vehicle System-of-System complex can implement in various military reconnaissance tasks.

Концепція "System of Systems" (SoS) для динамічних об'єктів стала дуже важливим напрямком в різних областях науки і промисловості, включаючи військову. SoS складається з компонентів, які вирішують одну задачуі в цілому, об'єднуючи власні властивості і можливості створюють комплексну систему з новими якостями. SoS – це така система, яка під час різних дій комбінує і об'єднує в собі синергетику команд, функцій управління, мережу і обмін інформацією зі зворотним зв'язком. У даній статті представлена розроблена програма бойового завдання польоту безпілотних літальних апаратів (БПЛА) SoS. Зазвичай, наземний центр управління БПЛА використовує радіозв'язок. Але це має свої недоліки: 1) радіозв'язок може порушитися, БПЛА не виконає завдання і в кращому випадку повернеться на базу; 2) ворог може порушити радіозв'язок і перехопити управління БПЛА. Створення БПЛА SoS комплексу обмежує ці недоліки. Відповідно до записаної в пам'ять програмного забезпечення, БПЛА SoS, використовуючиінфрачервоний радіозв'язок, є самоврядною системою, котра використовує принцип "feedback" і незалежно виконує бойове завдання. Якщо якийсь БПЛА втратить інфрачервоний радіозв'язок, тоді він (або вони) незалежно повернуться на базу. Якщо якийсь БПЛА буде збитий, інші продовжать свою місію. Отримано рівняння Гамільтона для руху даної системи. Запропоновано ІК зв'язок між БПЛА і радіозв'язок між БПЛА і наземним постом управління, а також умови управління польотом БПЛА. Показано, що комплекс БПЛА SoS може виконувати різні військові розвідувальні завдання.
Розробка програми бойового розвідувального завдання польоту безпілотних літальних апаратів SoS
Keywords: control system; infrared wireless; керуюча програма; інфрачервоний зв'язок